Air Power Proliferation: How Commercial-off-the- Shelf Drones are Being Used by Violent Extremist Organisations to Influence the Future of Warfare in the Air - Peers Lyle (Air and Space Power Review, 2019)
Air power, long the privilege of affluent state powers, is no longer inaccessible for Violent Extremist Organisations. ‘Commercial-off-the-shelf’ drones have enabled these organisations to build capabilities within the aerial domain. This is challenging the traditional dominance of air power that state powers have enjoyed and has consequences for both the forces operating on the battlefield and the within the world of air power studies. This article is a shortened version of a 15,000-word dissertation written as part of a MA in War Studies at King’s College, London. The longer version is available upon request.